Food industry shaping of the principles of scientific integrity. (20th October 2021) - Mialon, M; Ho, M; Carriedo, A; Ruskins, G; Crosbie, E
Abstract: Background: There is evidence that food industry actors try to shape science on nutrition and physical activity. But they are also involved in the influence of scientific integrity principles. Our research objective was to study the extent of that involvement, with a case study of ILSI as a key actor in that space. Methods: We conducted a qualitative document analysis, triangulating data from an existing scoping review, publicly available information, internal industry documents, and existing freedom of information requests. Results: Food companies have joined forces through ILSI to shape the development of scientific integrity principles. These activities started in 2007, in direct response to the growing criticism of the food industry's funding of research. ILSI first built a niche literature on conflicts of interest (COI) in food science and nutrition at the individual and study levels. Because the literature was scarce on that topic, these publications were used and cited in ILSI's and others' further work on COI, scientific integrity, and PPP, beyond the fields of nutrition and food science. In the past few years, ILSI started to shape the very principles of scientific integrity then and to propose that government agencies, professional associations, non-for-profits, and others, adopt these principles. In the process, ILSI built a reputation in the scientific integrity space. ILSI's work on scientific integrity ignores the risks of accepting corporate funding and fails to provide guidelines to protect from these risks. Conclusions: The activities developed by ILSI on scientific integrity principles are part of a broader set of political practices of corporations to influence public health policy, research, and practice. It is important to learn about and counter these practices as they risk shaping scientific standards to suit corporate interests rather than public health ones. Key messages: ILSI, a group funded by corporations, shaped the very principles of scientific integrity. ILSI built a reputation in the scientific integrity space.